Pengujian Karakteristik Unjuk Kerja Radiator - Prasetyo, Bambang Teguh (Program Studi Teknik Mesin, Universitas Trisakti, 2007)
Radiator Performance Characteristic Test. Test ofradiatorperformance characteristic atvarious flow rates has been done. The test is aimed to verify the specification given by vendor and todefine radiator performance, such as temperature effectiveness (e), Number of Transfer Unit (NTU) andpressure drop at around of design condition as a solution ofrating problem. Based onthe test results thisradiator was well designed. Temperature effectiveness variesaround60 to 85% and NTUshowed a goodagreement with the theoretical model. The different are around 0.1% to 5.3%>. Pressure drops are stillaccepted by design criteria. Especially for airside, the pressure drops arearound 29 to 392 Pa which arestill inferiorsthan 900Pa.